PENDIDIKAN ISLAM DAN JIHAD - Syamsul Kurniawan (Jurnal Pendidikan Islam, 2013)
This paper intends to specifically want to reveal the value of education in the spirit of true jihad includes the struggle in all aspects of life. The method used is the interpretation and hadith Tarbawi. After the September 11, 2001 in the U.S, the Islamic religion is often labeled as a brutal, militaristic, which declared war as a holy way. Though jihad into the spirit and the spirit of the teachings of Islam, is not synonymous with war (qital), because in the real jihad embodied educational values. Educational values contained fairly universal jihad, including the spirit of struggle in all aspects of life, including the struggle for moral and spiritual struggle to uphold truth and justice or commanding the good and forbidding the evil. Jihad build together without discrimination, to uphold justice and remove all forms of tyranny, greed and lust limit. This is the real meaning of jihad akbar well as the shape of the universe kerahmatan the ideals of Islam as hinted in Surah al - Anbiya ' (21): 107.